Pemanfaatan Limbah Cangkang Kelapa Sawit (Elaeis guineensis) Sebagai Pengadsorbsi Minyak Jelantah - Ubaidah, Nurcholis Al; Nuryanti, Siti; Supriadi, Supriadi (Universitas Tadulako, 2018)
Improper of usage and storage of cooking oil can increase the water content on cooking oil. It can decrease of cooking oil quality and fried food that resulted from this cooking oil which then can cause health problems. This study aimed to determine of the waste cooking oil quality after it was adsorbed with charcoal from eggshell palm oil (Elaeis gunieensis). The quality was determined based on the free fatty acids, the peroxide value, and the water content of the waste cooking oil before and after adsorption. Determination of free fatty acids was used titration method while determination of water content was used gravimetric method. The result showed that the cooking oil quality contained 0.014% of free fatty acids, 1 meq.O2/kg of peroxide value, and 0.0003% of water content. The waste cooking oil quality without adsorption process was 0.042% of free fatty acids, 26 meq.O2/kg of peroxide value, and 0.0011% of water content. After adsorption process with 5, 10, 15, 20, and 25 gram of charcoal from eggshell palm oil into 100 mL of waste cooking oil, it was found that 15 gram of eggshell weight was the best adsorbent. In was condition, the free fatty acid was 0.0006%, the peroxide value was 2 meq.O2/kg, and the water content 0.0005%. It showed that the waste cooking oil quality become better after adding of charcoal of eggshell palm oil as the adsorbent.